Photosynthetic Studies With Leaf Cell Suspensions From Higher Plants - Gnanam, A. (1969)
A technique for obtaining intact mesophyll cell suspensions derived from higher plant leaves is described. A large number of taxonomically unrelated plants were found suitable for cell `extraction' including several plant species from monocotyledonous group. The absorption spectra of leaf cells in suspension differed only slightly from that of Chlorella cells. The higher plant cells respired and photosynthesized in aqueous solutions very much like algal cell suspensions. Only osmotically intact cells photosynthesized maximally and their activity was stimulated by 2 to several fold by the addition of bicarbonate to the medium. The isolated cells when stored at low temperature with proper aeration maintained their initial activity for a minimum of 9 hr. Cells stored at the room temperature (27 ± 2°) lost their activity rather rapidly. The isolated cells were physiologically intact as tested by their metabolic response to diverse inhibiting chemicals and growth regulating substances.